Constitutional Law: Implikasi Bentuk Negara, Bentuk Pemerintahan dan Sistem Pemerintahan Terhadap Sistem Bernegara Belarusia - Yunus, Nur Rohim (BULETIN ADALAH, 2021)
Belarus is a unitary state situated in the Eastern European region. Belarus employs a presidential system of governance within its governmental framework. This implies that the president, who is elected directly by the populace, possesses the utmost executive authority. Nevertheless, there exists a role known as the prime minister, which has the responsibility of orchestrating the implementation of government programs on a daily basis. In Belarus, the government system establishes an equilibrium between the authority of the president as the chief executive and the prime minister as the chief executive. While the president wields significant authority, the prime minister plays a crucial role in overseeing the government's daily operations and facilitating the execution of policy. The Belarusian system of government exemplifies an endeavor to amalgamate components from several government systems, so establishing a distinctive model within the political and constitutional framework.